Two Sides of the Same Coin: Punishment and Forgiveness in Organizational Contexts - Van Houwelingen, Gijs; Van Dijke, Marius; Hoogervorst, Niek; Meijs, Lucas; De Cremer, David (Frontiers in Psychology, 2022)
Punishment and forgiveness are two very different responses to a moral transgression that both have been argued to restore perceptions of moral order within an organization. Unfortunately, it is currently unclear what motivates organizational actors to punish or forgive a norm transgressor. We build on social cognitive theory to argue that punishment and forgiveness of a transgressor are both rooted in self-regulatory processes. Specifically, we argue that organizational actors are more likely to respond to intentional transgressions with punishment, and to unintentional transgressions with forgiveness. However, these effects of transgressor intentionality should be found in particular among actors for whom moral identity is central (vs. peripheral). We find support for these predictions in a laboratory experiment and a field study among organizational leaders. By simultaneously studying punishment and forgiveness in organizational settings, we provide crucial insight in their shared motivational bases, as well as into important differences between the two.